State-Of-The-Art Ukrainian Equipment for Machine Welding of High-Pressure Pipelines of the Second Loop of NPP Units of Ukraine - Lobanov, L.M.; Makhlin, N.M.; Vodolazsky, V.Ye.; Korotynsky, О.Ye.; Zhernosekov, А.М.; Popov, V.Ye.; Skopiuk, М.І.; Lavrov, S.І.; Kudriashev, V.B. (Science and Innovation, 2024)
Introduction. High-pressure heaters (HPH) are principal components of the second loop of nuclear reactors with pressured water. HPH coils are used to heat water up to required temperature with its further supply to heat exchanger, steam generator (SG). Steam generated by SG is fed to turbines and triggers power generators of NPP unit. Problem Statement. The main factor that significantly constraints the performance of weld joints of HPH coil tubeworks while manufacturing and repairing and causes their defects is manual TIG welding method (hereinafter referred to as the TIG method) that has been used in the domestic practice so far. Purpose. To study ways of raising efficiency and performance of weld joints of HPH coil tubeworks and improving their stability and quality, as well as to develop domestic equipment for implementation of elaborated techniques. Materials and Methods. Steel 20 simulators of HPH tubeworks have been used for the purpose of the study. The used methods are as follows: mathematical and computer simulation full-scale modelling, trial welding, nondestructive and destructive control techniques, and CAD. Results. The use of various arc welding techniques for welding HPH coil tubeworks has been studied, the most optimal method of them, the most effective parameters of welding regimes, and requirements for domestic welding equipment have been identified, technical specifications for the equipment and its main components and respective research and predesign works have been developed, innovative technical proposals concerning its composition, configuration, structure, and other technical solutions have been elaborated. Conclusions. MIG + MAG welding method with the use of fused electrode (solid-section electrode wire) in protective gases mix has been established to be the most effective and cost-efficient in terms of compliance with the requirements of applicable norms and standards and approved technical specifications with respect to quality and performance of weld joints of HPH coil tubeworks made of steel 20. Manufacturing processes for the design solutions on the major functional nodes and mechanisms of the equipment for implementing the mentioned method have been developed and approved.